Results of the Gore Bio-A fistula plug implantation in the treatment of anal fistula: a multicentre study - Herold, Alexander; Vershenya, Stanislav (Techniques in coloproctology, 2016)
Background: The aim of this prospective study was to determine the efficiency of the Gore Bio-A synthetic plug in the treatment of anal fistulas. Methods: A synthetic bioabsorbable anal fistula plug was implanted in 60 patients. All fistulas were transsphincteric and cryptoglandular in origin. Results: The healing rate after 1 year of follow-up was 52 % (31 out of 60 patients). No patient was lost to follow-up. The treatment had no effect on the incontinence score. The plug dislodgement rate was 10 % (6 out of 60 patients). Thirty-four per cent of the patients (16 out of 47) required reoperation. The average operating time was 32 ± 10.2 min, and the average length of hospital stay was 3.3 ± 1.8 days. Conclusions: Synthetic plugs may be an alternative to bioprosthetic fistula plugs in the treatment of transsphincteric anal fistulas. This method might have better success rates than treatment with bioprosthetic fistula plugs.
Gesehen am 06.08.2019